Cefaleas - Silva R., Carlos; Venegas F., Pablo (Revista Hospital Clínico Universidad de Chile, 2009)
Headache is the most frequent symptom that makes patients to attend a neurologist’s office. Is a very common reason to attend general physician as well, so is very important to know how to do a correct diagnosis between primary and secondary headache and to treat the most frequent ones. This review includes migraine, tension type headache and others, from a clinical perspective, with special focuses on clinical clues that allow clinicians a more specific diagnosis and treatment. We want to emphasize how rational treatment should be prescribed and how to avoid rebound headache and others complications related to certain drugs, in particular ergotamines.